TEACHER STRATEGIES IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC: A PRACTICE IN ELEMENTARY SCHOOLS - Bagus Cahyanto; Mardiatus S. Lutfia; Nurul Muawana; Izza Nuriyah Ilmi (International Conference on Social and Islamic Studies, 2021)
During the Covid-19 pandemic, the learning process in elementary schools was carried out from home by utilizing online media. The practice of online learning certainly has advantages and disadvantages, so to support success and minimize the shortcomings of online learning, teachers need to create strategies that can be applied to online learning. This study aims to describe the strategies of elementary school teachers in online learning during the Covid-19 pandemic in second grade Madrasah Ibtidaiyah NU Sumberpasir. This study uses a descriptive approach with interview, observation, and documentation techniques for data collection. The results showed that the strategy teacher in online learning for the Covid-19 pandemic was to (a) time management, which is presenting assignment information every week on a regular basis to give students the opportunity to prepare and complete assignments early (b) flexibility, relating to the use of simple and easy learning platforms, (c) providing assistance and development of learning materials in a simple, clear, and attractive manner, (d) conduct regular learning, and (e) carry out periodic and continuous monitoring and evaluation of learning.